Prática da supervisão no processo ensinar-aprender em estágios supervisionados I e II do curso de enfermagem - Cerqueira, Isis Thamara de Argolo (2018)
The practice of supervision in Supervised Internships I and II of the Nursing course is part of the teaching / educating dimension of the nurse's work process. In this way, it is necessary that both teacher and student of nursing learn, understand and value knowledge about supervisory activities, as an action inherent to professional practice, the practice that should be developed in a efficient and effective way. This study has as objective to analyze the practice of supervision in the process of teaching and to learn in Supervised Internships I and II of the Nursing course through the eyes of the teachers and the students of an Institution of Higher Education. A qualitative and descriptive research was carried out, with the UEFS as the research field. The research had 19 participants, being 7 teachers and 12 students of the nursing course. The data collection techniques used were systematic observation, semi-structured interview and documentary analysis. The data were analyzed and interpreted through the Bardin Content Analysis. After careful reading of the data, the following categories were achieved: Supervision practice in the teaching-learning process in Supervised Stages I and II of nursing course: from traditional to social in the context of pedagogical tendencies; Difficulties and facilities of supervision practice in the teaching-learning process in Supervised Internships I and II of the nursing course. The practice of supervision in the teaching and learning process of SI I and II of the nursing course is permeated by social and traditional supervision, and permeates pedagogical trends problematizing and traditional / technical. The planning of actions takes place between the with functional and strategic supervision linked to social supervision. The teaching methodology of this process is influenced by the pedagogical tendencies traditional, technicist and problematizing. Teamwork, the role of the teacher, the communication and the implementation of activities are understood in the light of social problematizing pedagogy. The student's learning, content and role are influenced by the traditional and problematizing tendencies. Supervisory relationships between teachers, often take place in a quiet, harmonious and respectful way, with dialogue. In the evaluation of actions, social supervision occurs in the context of pedagogy traditional supervision associated with traditional and technical trends. The difficulties are due to the current situation of HEI, interfering negatively in SI; precariousness of nursing work and absence of preceptory; little or no communication among the teachers of the curricular components of the nursing course; absence of accompaniment of the teacher; lack of theoretical knowledge of students; among others. And facilities are communication and its instruments; the partnership with the team and the established relationship between teacher-student-team; the discussions between teacher and teacher; the possibility of proposing changes; and the content of supervision addressed in the curricular component of management. It is necessary to rethink the traditional / functionalist supervision and traditional and technical pedagogical practices adopted by teachers and students, as well as the enhancement of pedagogy problematic and social supervision for the practice of supervision in the process of teaching and to learn in the SI I and II of the nursing course in order to be promoted nursing actions based on SUS principles and guidelines. Difficulties are limits power to transform the practice of supervision into the process of teaching and learning